Islamic Religious Education Teacher Strategies Thru the SURJAN Program in Constructing Students' Religious Habitus in Coastal Vocational Environments: A Pedagogical and Neuroscience Analysis - Hariyanto Hariyanto; Suyadi Suyadi; Sri Roviana (Early Publishing, 2025)
This research is motivated by the challenge of moral degradation among adolescents in the era of technological disruption and the low level of early religiosity among students in coastal vocational schools. Data shows that 75% of students do not perform mandatory prayers at home, and the majority are not yet proficient in reading the Quran. This research aims to analyze the strategy of Islamic Religious Education (PAI) teachers in fostering students' religious character through the flagship program of sujud, rajin, and ngaji (SURJAN) at SMKN 1 Tepus. The method used is qualitative with a case study type. The research results indicate that the PAI teachers' strategy is implemented through three pillars of SURJAN, namely, first, sujud (habit of praying in congregation), second, rajin (5S culture and industrial discipline), and third, ngaji (reading the Quran). The impact of this strategy is an increase in the frequency of mandatory prayers at home by up to 80% and an improvement in the ability to read the Quran.